A Multidisciplinary Approach to Rectal Cancer Treatment in Ulcerative Colitis Results in High Rate of Restorative Minimally Invasive Surgery. (4th August 2021) - Carvello, Michele; Bellato, Vittoria; Maroli, Annalisa; Hart, Ailsa; Danese, Silvio; Warusavitarne, Janindra; Spinelli, Antonino
Abstract: Background and Aims: Few recent studies focus on the treatment of rectal cancer in patients with ulcerative colitis. We report treatment options and results for this subset of patients with a multimodal approach at two European referral centres. Methods: Ulcerative colitis patients diagnosed with rectal cancer arising at less than 15 cm from the anal verge between January 2010 and December 2020 were analysed. Demographics, clinical data, and details of medical and surgical treatment were retrieved from prospectively collected institutional databases. Results: Of 132 patients with ulcerative colitis and concomitant colorectal cancer, rectal cancer was diagnosed in 46. The median time between disease onset and rectal cancer diagnosis was 17.5 years; 21/46 were preoperatively staged as early tumours [cT1-T2/N0]. Eleven patients received neoadjuvant chemoradiotherapy for locally advanced extraperitoneal adenocarcinoma, and the rest underwent surgery first. Over two-thirds of the procedures were restorative [68%]; a minimally invasive approach was used in 96% of patients, with no conversion to open. The median follow-up was 44 months. Local recurrence occurred in three patients [6%]. The cumulative 3-year cancer-specific survival rate was 94% [and the 3-year disease-free rate was 86%]. Conclusions: Rectal cancer in ulcerative colitis is a very complex condition. Our results show that surgery for rectal cancer can be delivered with excellent oncological and functional outcomes in patients with ulcerative colitis. A multidisciplinary discussion among surgeons, gastroenterologists, and medical oncologists is key to ensure the appropriate treatment pathway for individual patients.